Medical and anesthesia students' attitude toward e-learning physiology courses during the COVID-19 pandemic days - Reza Yahyavi Sahzabi; Fatemeh Maghsoudi; Elahe Akjavan; Sara Mobarak; Esmat Radmanesh (Tabriz University of Medical Sciences, 2022)
Background: The alarming outbreak of the COVID-19 virus significantly disrupted all aspects of human life, including education. As a result, e-learning has become a vital tool for education. This study aimed to investigate the attitudes of medical and anesthesia students toward e-learning in physiology during the pandemic of COVID-19. Methods: This descriptive study was conducted among 67 medical and anesthesiology students at Abadan University of Medical Sciences who studied physiology in the second semester of 2020-2021 in the form of e-learning due to the COVID-19 pandemic. A researcher-created questionnaire was used, rating items on a five-point Likert scale. Data were entered into SPSS 21 for statistical analysis and analyzed using descriptive statistics. Results: A total of 73.1% of the participants in this study were women. The favorable opinions of students by percentage were as follows: satisfactory access to the Internet, 71.0%; the possibility of downloading educational content from the educational system, 88.2%; effective communication between teacher and student through e-learning, 20.6%; e-learning by combining online and offline education, 69.1%; the suitability of offline educational content due to accessibility convenient to learn at any time and place where the student wants to learn, 75%; face-to-face education is more suitable than e-learning, 60.3%. Conclusion: Effective communication between teacher and student is weak in virtual/online education. Students were generally positive about a combination of online and offline virtual education together and liked offline educational content due to ease of access at any time and place. In general, students preferred face-to-face teaching to virtual education.